The difficulties & challenges that hinder successor’s learning in Chinese family business succession : an institutional theory-based view - Chew, Kean Leng (2017)
By employing an Institutional-Theory-based view, this study delves deeper into the multiphase action plan of intergenerational succession to critically assess the determinants which contribute to Successors’ cognitive development in Chinese family business succession, as well as other contextual nuances which could affect the overall learning experience. Through four unique case studies derived from qualitative interview data, this study assesses the on-going succession plan and characteristics of actors for each family businesses engaged. The findings firstly establish that the Successor’s learning experience is institutionalized while in China’s environment; and that there is an associative relationship across all regulatory, cognitive and normative dimensions of institutions, thus, explaining how influences towards both actors’ cognitions and norms manifest. Furthermore, institutional influences that manifest due to the Confucian ideology acts like a double-edged sword. The belief of family interests above self-interests heightens the Successor’s motivation to learning and accepting of succession; while, despite the belief of obedience to elders gave rise to the importance of supporters in the succession process, it also risks causing Successor burnout. Therefore, by practicing vigilance in affirmatively developing measures to address institutional influences, the Successor’s learning experience during succession can be managed appropriately, thus, driving the succession agenda.